Peran Lembaga Kegiatan Pengajian Baca Al-Qur’an Dalam Pembinaan Moral Anak Di Desa Mabolu Kabupaten Muna Sulawesi Tenggara - Melisa Saputri; Hamsah Hamsah; Sangputri Sidik (PT. Citra Media Publishing, 2025)
This study aims to describe the role of Al-Qur'an recitation activities in the moral development of adolescents in Maabholu Village using a descriptive qualitative research approach. Data collection techniques, observation, interviews, and documentation were used to obtain the following results: data collection on congregations and guidance teachers, facilities and infrastructure, activities during recitation sessions, and the annual program of the Al-Akbar Mosque Recitation Institution. In overcoming the obstacles faced by the study group administrators in shaping the morals of adolescents, they provide guidance to adolescents through examples such as lectures, providing examples of positive activities, providing knowledge about religion, and increasing activities related to da'wah (proselytizing). The types of activities for shaping the morals of youth at the Al-Akbar Religious Institute include recitation of verses from the Holy Qur'an, recitation of Yasin, tahlil, zikir, and 10-minute lecture practice. The inhibiting factors are the low attendance of teenagers, lack of motivation from parents, and the development of technology and communication media, especially gadgets and the internet, which prevent teenagers from fully absorbing the material. Talking during the recitation. The character building of teenagers implemented at the Al-Akbar Mosque Institute includes the story method, the mauidzah (advice) method, the caramah method, and the question and answer method.